J-Analyzer: A Software for Computer-Assisted Analysis of Antônio Carlos Jobims Songs - Almada, Carlos; Penchel, João; Chagas, Igor; Kühn, Max; Usai, Claudia; Cabral, Eduardo; Braga, Vinicius; Miccolis, Ana (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
The present paper describes structure and functioning of J-Analyzer, a computational tool for assistedanalysis. It integrates a research project intended to investigate the complete song collection by Brazilian composer Antônio Carlos Jobim, focusing on the aspect of harmonic transformation. The program is used to determine the nature of transformational relations between any chordal pair of chords present in a song, as well as the structure of the chords themselves.